Beyond narrative: a pedagogical, cultural, and psychological analysis of Saken Zhunusov’s Amanai and Zamanai for higher education - Tokzhan Igenbay; Gauhar Baltabaeva; Amangaisha Bolsynbayeva; Gulnara Apeyeva; Sarash Konyrbayeva (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study offers a comprehensive pedagogical analysis of Saken Zhunusov’s Amanai and Zamanai, demonstrating that the novella functions as a multilayered educational text suitable for literature, cultural studies, teacher education, and psychology-of-literature curricula in higher education. Using qualitative content analysis, the study identifies six interrelated thematic domains; moral education, cultural learning, developmental psychology, folklore pedagogy, narrative methodology, and emotional literacy, through which the novel teaches readers to interpret emotional, ethical, and cultural meanings embedded in the narrative. The data consisted of the full text of Saken Zhunusov’s Amanai and Zamanai, analyzed using qualitative content analysis. Findings reveal that the text models moral dilemmas, cultivates empathy, preserves Kazakh cultural knowledge, exposes structural inequalities, and illustrates childhood cognition and trauma through symbolic and myth-infused storytelling. The study connects these themes to established theoretical perspectives including Vygotsky’s symbolic mediation, Bruner’s narrative cognition, Rosenblatt’s reader–response theory, and cultural-historical views of oral tradition. By developing a detailed codebook and pedagogical framework, the research provides a replicable model for analyzing culturally embedded literature and demonstrates the relevance of Amanai and Zamanai to contemporary Kazakh social issues such as poverty, gendered burden, and generational trauma. The study concludes that the novel offers rich opportunities for interdisciplinary teaching and contributes significantly to the integration of Kazakh literature into modern higher education pedagogy.